Euler’s Equations of Motion by using interval function - et. al., J.Hellan Priya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Euler's Equations of Motion play a role in deciding the approximated solution to that same interval valued problem. The interval valued Euler equations are added and extracted. Euler's Equations are used to determine the shortest path a particle may follow from one location to another location within single-variable functions. When discussing the motion of the particle and its direction, the relationship between the points on the surface and the coordinates of the particle may be investigated.